Regional and Seasonal Variations in Snow-Cover Density in the U.S.S.R - Bilello,M A (1984)
Regional seasonal variations in snow-cover density (SCD) in the U.S.S.R. were determined through the analysis of data obtained from all available Soviet literature. A relationship found between observed winter wind speeds and SCD values recorded from November through March made it possible to develop a snow-density map of the U.S.S.R. The map was divided into five general categories of SCD, ranging from values of or = 0.21 g/cu cm at interior stations with very light winds to values of or = 0.31 g/cu cm at arctic locations with strong winds. Since this literature survey indicated that the reported Soviet SCD values were incorrect due to instrumental errors, adjustments to the data in this study were required. Month-to-month investigation of the SCD data revealed a gradual increase in density from November to March and that the SCD values under forest canopies averaged from 4 to 14% lower than those recorded in open areas. Also included in this report are (1) a compilation of pertinent passages in the Soviet literature on SCD, (2) a map showing the location of SCD measurements, and (3) an average winter wind speed chart for the U.S.S.R.